Systematic review on the effectiveness of self-applied interventions in sexual health - Rodríguez-Rodríguez, Fernando (2025)
The objective of this research is to conduct a systematic review on the effectiveness of self-administered interventions in sexual health. An analysis of peer-reviewed publications covering the period from 2013 to 2023 was carried out in four databases: PubMed, Web of Science, Scopus, and Medline. A preliminary 693 articles were found; after the screening process, 17 articles met the inclusion criteria. The approaches and means implemented by some studies to address the prevention of STIs were to integrate mobile technology and the development of online applications, in which self-efficacy programs were generated to develop skills for the rejection of sexual risk behaviors, substance use, and increased STI/HIV testing, in addition to improved communication, feedback, increased knowledge, promotion of HIV testing, risk assessment, and connection to health services. It was found that the interventions analyzed used various means for their implementation, such as online, mobile phone, manual distribution, or video. The results of the interventions have positive effects by increasing the frequency of HIV testing, reducing unprotected sex, improving knowledge and awareness about STIs and HIV, as well as generating changes by strengthening self-efficacy and decision-making related to sexual health. These findings show the importance of contributing with self-applied interventions to promote sexual health and reduce health problems, such as STIs.